Comparative study of proline accumulation of Some varieties of Durum Wheat (Triticum durum Desf.) under water Stress Conditions. - Yasmina Semiani; Marie Stella Bradea; Abdelkader Benbelkacem; Mohammed Semian (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Agriculture, 2016)
Proline accumulation, as a marker of resistance to the abiotic constraints, was evaluated on seventeen genotypes of Durum wheat (Triticum Durum Desf) under water stress conditions. An experiment was implemented at INRAA research station located at Baraki, Algiers. The experimental design adopted is that of split plot design with water regime (irrigated and non irrigated treatments) as main plots and varieties as sub plots and three repetitions. Proline accumulation was significantly increased under water stress (p<0.01). There was differences between varieties and their interaction with water regimes (p<0.001) and 04 groups were identified. When plants are subjected to water stress they increase their rate of proline, this enables to improve the capacity of the cell to maintain it turgor pressure at low water potential.